Introduction to C# programming - Pomeprada, Jake R. (Intramuros, Manila : Mindshapers, 2018)
"This book deals with the introduction of C# programming language for beginner programmers, student and anyone who are interested to learn C# programming languages. In this book, I will also discuss most common mistakes committed by beginners in learning C# programming" -- Preface
Chapter 1: Programming concepts -- Chapter 2: Introduction to C# language -- Chapter 3: Conditional statements --Chapter 4: Looping statements -- Chapter 5: Methods --Chapter 6: Arrays -- Chapter 7: String -- Appendix A: Address book database application -- Appendix B: Login security system -- References
Includes appendices and bibliographical references.
Keywords: C# (COMPUTER PROGRAM LANGUAGE